English Catholic exiles in late sixteenth-century Paris - Gibbons, Katy (Woodbridge [u.a.] Royal Historical Society, Boydell Press, 2011)
This title uses a range of evidence to investigate the polemical and practical impact of religious exile. Moving beyond contemporary stereotypes, it reconstructs the experience and the priorities of the English Catholics in Paris and the hostile and sympathetic responses that they elicited in both England and France
Introduction -- The home and host contexts for Elizabethan exiles -- Between civility and piety: exile niches in an urban environment -- Exile in action: communicating and propagating the cause of radical Catholicism -- Making sense of exile: alternative and competing representations -- Returning or remaining? Divisions and longer-term developments in English Catholicism -- Conclusion
Introduction -- The home and host contexts for Elizabethan exiles -- Between civility and piety: exile niches in an urban environment -- Exile in action: communicating and propagating the cause of radical Catholicism -- Making sense of exile: alternative and competing representations -- Returning or remaining? Divisions and longer-term developments in English Catholicism -- Conclusion.
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Catholics -- France -- Paris -- History -- 16th century; English -- France -- Paris -- History -- 16th century; Exiles -- France -- Paris -- History -- 16th century; Reformation -- Europe; France -- Church history -- 16th century; England -- Church history -- 16th century; Catholics -- France -- Paris -- History -- 16th century; English -- France -- Paris -- History -- 16th century; Exiles -- France -- Paris -- History -- 16th century; Reformation -- Europe; England -- Church history -- 16th century; France -- Church history -- 16th century